Asymmetrical Warming Between Elevations May Result in Similar Plant Community Composition Between Elevations in Alpine Grasslands - Wang, Jiangwei; Yu, Chengqun; Fu, Gang (Frontiers in Ecology and Evolution, 2021)
Asymmetrical warming between elevations is a common phenomenon and warming magnitude increases with increasing elevations on the Tibetan Plateau, which in turn may reduce temperature differences between elevations. However, it is still unclear how such phenomenon will affect plant community composition in alpine grasslands on the Tibetan Plateau. Therefore, in this study, we performed an experiment at three elevations (i.e., 4,300 m, 4,500 m, and 4,700 m) in alpine grasslands, the Northern Tibetan Plateau since May, 2010. Open top chambers were established at the elevations 4,500 m and 4,700 m. Plant species and phylogenetic composition were investigated in August, 2011–2019. There were no significant differences in plant species and phylogenetic composition, environmental temperature and moisture conditions between the elevation 4,300 m under non-warming conditions and the elevation 4,500 m under warming conditions in 2019. There were also no significant differences in plant species composition, environmental temperature and moisture conditions between the elevation 4,500 m under non-warming conditions and the elevation 4,700 m under warming conditions in 2019. Therefore, the narrowing temperature differences between elevations may result in plant community composition between elevations tending to be similar in alpine grasslands on the Tibetan Plateau under future elevational asymmetrical warming.